2007
DOI: 10.1002/jtr.619
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Singapore travel agencies' customer loyalty: an empirical investigation of customers' behavioural intentions and zones of tolerance

Abstract: The services marketing literature focuses on the measurement of service quality and its impact and consequences on businesses. Set in the context of the travel retail agency in Singapore, this study focuses on the relationship between service quality and favourable behavioural intentions. The findings revealed that improving service quality can increase favourable behavioural intentions. However, service improvements that exceed customers' minimum-service threshold and those that exceed customers' desired-serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…A positive linear pattern such that there is no difference in the positive slope across different levels of the ZOT (e.g., Zeithaml et al 1996;Teas and DeCarlos 2004;Lobo et al 2007;Yap and Sweeney 2007), as shown in Figure A1.…”
Section: The Zone Of Tolerance (Zot)mentioning
confidence: 99%
“…A positive linear pattern such that there is no difference in the positive slope across different levels of the ZOT (e.g., Zeithaml et al 1996;Teas and DeCarlos 2004;Lobo et al 2007;Yap and Sweeney 2007), as shown in Figure A1.…”
Section: The Zone Of Tolerance (Zot)mentioning
confidence: 99%
“…Walker and Baker (2000) indicated that the concept of ZOT could offer managers useful information for improving service quality. Some scholars explored the ZOT theory from a managerial application perspective (such as Cook et al, 2003;Van Riel et al, 2003;Kettinger and Lee, 2005;Nadiri and Hussain, 2005;Cavana et al, 2007;Lobo et al, 2007). Yap and Sweeney (2007) suggested a moderating role for the ZOT in the quality-key outcomes relationship.…”
Section: Zone Of Tolerance Of Expectationmentioning
confidence: 99%
“…Gilbert and Gao (2005) examined the relationships between customer tolerance and customer experience, brand trust and customer emotions for travel agencies. Lobo et al (2007) used minimum and desired service expectations and the zone of tolerance to investigate the relationship between service quality and behavioural intentions. Cavana et al (2007) used the multi-expectation framework and zone of tolerance approach to evaluate passenger rail service quality.…”
Section: Literature Reviewmentioning
confidence: 99%